Distinctive analysis of power and frequency allocation for Device to Device (D2D) communication. (March 2023) - Turaga, Hemanth; Bommisetty, Sree Harsha; Vanukuru, Charan; S, Nandakumar; Preetha, K.S.; Velmurugan, T.
Abstract: Wireless communication makes an impeccable advancement from 1 G to 5 G and beyond. Simultaneously, modern technologies like Internet of Things (IoT) and Vehicular Communications also emerged. Improved connectivity between many different devices is provided by 5 G, which maximises data throughput and reduces interference. Non-Orthogonal Multiple Access (NOMA) schemes or Orthogonal Multiple Access techniques (OMA) suit 5 G. It is a NOMA-based device-to-device communication by correlating it with the Orthogonal Frequency Division Multiple Access (OFDMA). NOMA is also utilized to propose an optimal power allocation scheme and duly evaluated. The aim of such a scheme is to achieve a minimized outage and a maximized sum rate. A NOMA based Greedy Interference Algorithm is proposed for interference management by exquisite frequency allocation. The results generated from a comprehensive evaluation justify the algorithm utilization. Simulation results infer that the algorithms proposed improves system throughput and enhance energy efficiency.